beta-lactamase production Haemophilus spp. and resistance to ampicillin in a general hospital in Porto Alegre city, RS, Brazil (2001-2005) - Ferreira,Jorge A. S. (2007)
In a four-year period (July/2001-June/2005), 410 Haemophilus spp. isolates were studied. Those were isolated from sputum at Hospital Nossa Senhora da Conceição (NSC) in Porto Alegre city (RS). beta-lactamase enzyme was detected in 113 (27.6%) of isolates through chromogenic cephalosporin method. Fifty-eight (51.3%) of them showed sensibility to ampicillin through disc-diffusion method using Haemophilus Test Medium (HTM) by NCCLS criteria. In 297 (72.4%) isolates beta-lactamase was not detected by chromogenic cephalosporin method. Five (1.7%) of them were resistant and 1 (0.3%) intermediate to ampicillin using disc-diffusion method. The authors emphasized the importance of Haemophilus spp. resistance to ampicillin research in clinical laboratories routine and the use of more than one method for this analysis was proposed, due to different resistance mechanisms in Haemophilus spp.